2018
DOI: 10.1002/jpen.1174
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Syringe Compression Force Between ENFit and Legacy Feeding Tubes

Abstract: Overall, only a small number of tube sizes (14Fr and 20Fr) with selected formulas revealed a significant difference between ENFit and Legacy tubes, with remaining studies finding no significant difference. Regression analysis revealed that variables such as formula, size of tube, blender used, and time of blending may have more impact on compression force.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…The use of an RDN was much higher in the pediatric cohort (73.5%). Our previous evaluation of the force required to compress a syringe with ENFit tubes vs legacy tubes revealed that tube size, type of blender, and time of blending all had an impact on the force required to compress a syringe . In the present study, the vast majority of pediatric BTF consumers were using 18F or smaller tubes and likely will not be impacted with this transition, as no one reported using a 24F or 26F tube.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…The use of an RDN was much higher in the pediatric cohort (73.5%). Our previous evaluation of the force required to compress a syringe with ENFit tubes vs legacy tubes revealed that tube size, type of blender, and time of blending all had an impact on the force required to compress a syringe . In the present study, the vast majority of pediatric BTF consumers were using 18F or smaller tubes and likely will not be impacted with this transition, as no one reported using a 24F or 26F tube.…”
Section: Discussionmentioning
confidence: 50%
“…The commonly used sizes also have an impact on the transition to the ISO 80369‐3 connector. We recently evaluated the most common connector to meet this standard (ENFit), using feeding scenarios common to HEN patients such as gravity feeding and syringe feeding . After testing a wide variety of formulas, we noted no significant impact of ENFit transition on 18F and 20F tubes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations